1999
DOI: 10.1037/0893-3200.13.4.580
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and marital functioning: Comparison of spouses with continuous-secure, earned-secure, dismissing, and preoccupied attachment stances.

Abstract: We gratefully acknowledge Sami Hanks for her continued efforts on this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
107
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(126 citation statements)
references
References 45 publications
16
107
1
2
Order By: Relevance
“…The evidence that a secure generalized representation is associated with better marital behavior and functioning is not as clear as one would hope (e.g., Crowell & Treboux, 2000;Crowell, Treboux, Gao, et al, 2002;Kobak, 1991;Paley et al, 1999). The findings do not speak well to the criticism raised by Karney and Bradbury (1995) about the course of relationships; for example, security of generalized attachment representations does not predict divorce and separation very well, a key issue in the marital field.…”
Section: Attachment Security As a "Trait"mentioning
confidence: 87%
“…The evidence that a secure generalized representation is associated with better marital behavior and functioning is not as clear as one would hope (e.g., Crowell & Treboux, 2000;Crowell, Treboux, Gao, et al, 2002;Kobak, 1991;Paley et al, 1999). The findings do not speak well to the criticism raised by Karney and Bradbury (1995) about the course of relationships; for example, security of generalized attachment representations does not predict divorce and separation very well, a key issue in the marital field.…”
Section: Attachment Security As a "Trait"mentioning
confidence: 87%
“…Because of their heavy investment in emotional relationships, and because of difficulties regarding affect regulation (e.g., Kobak & Sceery, 1988), we predicted that preoccupied individuals would display less positive and more negative behavior than dismissing individuals. Although this hypothesis has received some support by researchers using attachment orientation measures (e.g., Feeney, Noller, & Callan, 1994), research involving interview-based attachment methods has documented similar patterns of conflict negotiation between preoccupied and dismissing adults (Paley et al, 1999).…”
Section: Adult Attachment Researchmentioning
confidence: 99%
“…Simpson et al (1996) had respondents evaluate perceptions of attachment behaviors in romantic relationships (e.g., "I don't like people getting too close to me") and found that general insecurity in such relationships (avoidance in men, ambivalence in women) predicted conflict management difficulties with romantic partners during a problemsolving task. Finally, Paley, Cox, Burchinal, and Payne (1999) documented that adults with secure IWM displayed fewer problems managing conflict in a problem-solving task than did insecure adults. It is interesting that preoccupied and dismissing adults displayed conflict management problems with equal frequency.…”
Section: Adult Attachment Researchmentioning
confidence: 99%
“…What happens, for example, when an individual with a dismissing state of mind regarding attachment becomes involved in an intense relationship with an individual with a preoccupied or secure state of mind? Intriguing research has begun to tackle these questions (Cowan & Cowan, 2001;Crowell & Treboux, 2001;Paley, Cox, Burchinal, & Payne, 1999;Treboux et al, 2004), but far more remains to be done.…”
Section: The Complexity Of Attachment Relationships Beyond Childhoodmentioning
confidence: 99%